Sustainable futures in indigenous architecture: a study of contemporary professional engagement with mud techniques in Nigeria - Adetoro, Olufunmilayo Comfort; Gambo, Emmanuel Bamidele (Frontiers in Built Environment, 2025)
The Nigerian building industry faces a dual challenge of environmental unsustainability and cultural erosion. This study examines contemporary professional engagement with mud techniques among architects practising on Lagos Island, an area symbolic of rapid urbanisation and cultural transition. A quantitative survey method was employed, using questionnaires distributed to architects, with results analysed through descriptive statistics. The findings reveal increasing awareness of mud’s ecological and cultural benefits; however, adoption remains limited due to concerns over durability, lack of technical innovation, and regulatory uncertainty. While many respondents recognised mud’s sustainability potential, outdated perceptions and weak policy frameworks continue to hinder its mainstream application. The study recommends targeted policy interventions, professional capacity building, and curriculum reform to reposition mud architecture as a viable, sustainable option within Nigeria’s construction sector.